Wallfahrer in Mexiko - eine Form traditionellen Fremdenverkehrs zwischen kultischer Ökonomie und Tourismus - Tyrakowski, Konrad (ERDKUNDE, 1994)
This article aims at demonstrating the momentum of regions outside Mexico’s metropolit an areas in the field of pilgrim traffic. In this context a pattern of spatial behaviour is in the making that creates its own flows of traffic by using handed-down pilgrims’ ways with a hierarchy of nodal points independent of the normal network of central places. This system receives stimuli from its historical embodiment and from the piety, deeply rooted in the people, following its own specific rules. Though meeting some formal criteria of modern tourism the Mexican pilgrim traffic should be kept apart from the former’s way of travelling. Pilgrimages are by no means spare-time activities: there is too great a difference in its motives, and the pilgrims’ expenses are too high. The main impetus is something called ritual economy, i. e. a mutual relationship of give and take that develops between the heavenly powers and the pilgrim, between the churchwardens and the parishioners. Its ethno-historical and its social roots, its economic effects and its impulses toward creating a national identity are outlined using the following places of pilgrimage as examples - Guadalupe/Mexico City, Chalma /Mexico State, San Miguel del Milagro/Tlaxcala.